Going beyond the equilibrium crystal shape: re-tracing the morphological evolution in group 5 tetradymite nanocrystals. Issue 37 (15th September 2021) - Hwang, Woohyun; Yoo, Su-Hyun; Soon, Aloysius; Jang, Woosun
Abstract : Tuning the nanomorphology of group 5 tetradymite M2 X3 (where M = Bi and Sb, and X = Se and Te) by going beyond thermodynamic equilibrium. Abstract : Nanocrystals of group 5 tetradymites M2 X3 (where M = Bi and Sb, X = Se and Te) are of high technological relevance in modern topological nanoelectronics. However, there is a current lack of a systematic understanding to predict the preferred nanocrystal morphology in experiments where commonly-used equilibrium thermodynamic models appear to fail. In this work, using first-principles DFT calculations with a rationally-extended ab initio atomistic thermodynamics approach coupled to implicit solvation models and Gibbs–Wulff shape constructions, we demonstrate that this absence of predictive power stems from the limitation of equilibrium thermodynamics. By re-tracing and carefully addressing with a more realistic chemical potential definition, we illustrate this shortcoming can be overcome and afford a more rational route to size-engineer and shape-design highly-functional group 5 tetradymite nanoparticles for targeted applications.